2015
DOI: 10.1177/0956797615604124
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Fear Learning Depends on Empathic Appraisals and Trait Empathy

Abstract: Empathy and vicarious learning of fear are increasingly understood as separate phenomena, but the interaction between the two remains poorly understood. We investigated how social (vicarious) fear learning is affected by empathic appraisals by asking participants to either enhance or decrease their empathic responses to another individual (the demonstrator), who received electric shocks paired with a predictive conditioned stimulus. A third group of participants received no appraisal instructions and responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 45 publications
(66 reference statements)
11
56
0
Order By: Relevance
“…Based on studies in rodents showing that exposure to a frightened conspecific triggers an observer’s distress and fear, an argument has been made for the involvement of affective sharing/empathy as a critical factor in the transmission of fear information and the ensuing learning [41, 53]. This is consistent with a recent experiment in humans showing that a simple instruction manipulation that has been previously validated to enhance empathy with a target (encouraging the observer to pay close attention to a demonstrator’s discomfort during the application of “painful” electric shocks) augmented fear learning acquired through observing a demonstrator receiving electric shocks [54]. Research on empathy and pro-social behaviors in humans suggests that individuals expressing high levels of empathy learn pro-social behaviors faster [55].…”
Section: Social Cognition and Sflsupporting
confidence: 74%
“…Based on studies in rodents showing that exposure to a frightened conspecific triggers an observer’s distress and fear, an argument has been made for the involvement of affective sharing/empathy as a critical factor in the transmission of fear information and the ensuing learning [41, 53]. This is consistent with a recent experiment in humans showing that a simple instruction manipulation that has been previously validated to enhance empathy with a target (encouraging the observer to pay close attention to a demonstrator’s discomfort during the application of “painful” electric shocks) augmented fear learning acquired through observing a demonstrator receiving electric shocks [54]. Research on empathy and pro-social behaviors in humans suggests that individuals expressing high levels of empathy learn pro-social behaviors faster [55].…”
Section: Social Cognition and Sflsupporting
confidence: 74%
“…Additional activations were observed in anterior insula (AI), ACC, and dorsolateral prefrontal cortex (dlPFC) (Olsson et al, 2007)—regions involved in the processing of pain, empathy, and other emotions. The authors concluded that the observation of a distressed conspecific can act like an unconditioned stimulus—especially for highly empathic individuals (Olsson et al, 2015)—, and thereby engages similar pathways as direct classical conditioning (Olsson et al, 2015; Olsson and Phelps, 2007). Conversely, both direct and vicarious fear extinction involve vmPFC-amygdala interactions (Golkar et al, 2016).…”
Section: Social Information Effects On Pain and Emotionmentioning
confidence: 99%
“…In social species, like humans, knowledge about threats and dangers is often acquired through various forms of social transmission, for example through observation. Research across species has shown that observing a conspecific's -a "Demonstrator's" -threat responses to a previously neutral stimulus can cause strong and persistent threat memories in the "Observer" [1][2][3][4][5][6][7][8][9][10][11][12]. Such memories are expressed by heightened autonomic nervous system activity in the observer when later facing that stimulus alone.…”
mentioning
confidence: 99%
“…For observational learning to occur, the demonstrator's reactions to the threatening stimulus must function as unconditioned stimulus for the observer. It has been hypothesized that empathic processes, enabling the sharing or understanding of affective states between demonstrator and observer, facilitate observational learning [4,10,[14][15][16][17]. Previous work has implicated trait measures of cognitive empathy in observational learning [10,18], emphasizing the role individual differences in the observer's capacity to take the perspective of the demonstrator plays in learning.…”
mentioning
confidence: 99%